Efficacy of venetoclax in high risk relapsed mantle cell lymphoma (MCL) ‐ outcomes and mutation profile from venetoclax resistant MCL patients. Issue 6 (17th April 2020) - Zhao, Shuangtao; Kanagal‐Shamanna, Rashmi; Navsaria, Lucy; Ok, Chi Young; Zhang, Shaojun; Nomie, Krystle; Han, Guangchun; Hao, Dapeng; Hill, Holly A.; Jiang, Changying; Yao, Yixin; Nastoupil, Loretta; et al.
Abstract: Venetoclax is effective in relapsed patients with mantle cell lymphoma (MCL). Mechanisms of resistance to venetoclax in MCL are poorly understood. We describe the clinical outcomes and genomic characteristics of 24 multiply relapsed patients (median of five prior lines of therapy) who received venetoclax‐based therapies; 67% had progressed on BTK inhibitors (BTKi) and 54% had blastoid or pleomorphic histology. Median follow up after venetoclax treatment was 17 months. The overall response rate was 50% and complete response (CR) rate was 21%, 16 patients had progressed and 15 died. The median progression free, overall and post venetoclax survival were 8, 13.5 and 7.3 months respectively. Whole‐exome sequencing (WES) was performed on samples collected from seven patients (including five pairs; before starting venetoclax and after progression on venetoclax). The SMARCA4 and BCL2 alterations were noted only after progression, while TP53, CDKN2A, KMT2D, CELSR3, CCND1, NOTCH2 and ATM were altered 2‐4‐fold more frequently after progression. In two patients with serial samples, we demonstrated clonal evolution of novel SMARCA4 and KMT2C/D mutations at progression. Mutation dynamics in venetoclax resistant MCL is demonstrated. Our data indicates that venetoclax resistance in MCL is predominantly associated with non‐BCL2 gene mutations. Further studies are ongoing in MCL patients to evaluate the efficacy of venetoclax in combination with other agents and understand the biology of venetoclax resistance in MCL.